Dot‐Blotting: A Quick Method for Expression Analysis of Recombinant Proteins. Issue 9 (12th September 2022) - Mishra, Vibhor
Abstract: Expressing recombinant proteins in heterologous host cells is a prerequisite for purification and other downstream processes. Cell cultures require a protein expression test to optimize incubation time, temperature, and additives (like chemical inducers) to identify the best growth conditions with maximum recombinant protein yield. However, running SDS‐PAGE followed by western blotting is cumbersome and results are not quick. Here, I describe a simple protocol to quickly check the presence of recombinant protein in cell cultures using a dot‐blot experiment. The cells can be rapidly lysed and directly spotted on the nitrocellulose membrane. Then, the membrane is incubated with a horseradish peroxidase (HRP) conjugated antibody raised against the affinity tag present on the recombinant protein to confirm the protein expression by chemiluminescence. It takes less than an hour to get results. This method rapidly investigates recombinant protein expression in different cell lines and tests other variables. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Protein expression analysis for eukaryotic systems Basic Protocol 2 : Protein expression analysis for bacterial systems